Factorization of Quadratic Trinomials

In factorization of quadratic trinomials there are two forms: 

(i) First form: x2 + px + q

(ii) Second form: ax2 + bx + c

(i) Factorization of trinomial of the form x^2 + px + q:

Suppose we are given a quadratic trinomial x2 + px + q.

Then, we use the identity:

x2 + (a + b) × + ab = (x + a)(x + b).


Solved examples on factorization of quadratic trinomials of the form x^2 + px + q:

1. Factorize the algebraic expression of the form x2 + px + q:

(i) x2 - 7x + 12

Solution:

The given expression is x2 - 7x + 12

Find two numbers whose sum = -7 and product = 12

Clearly, such numbers are (-4) and (-3).

Therefore, x2 - 7x + 12 = x2 - 4x - 3x + 12

                                = x(x - 4) -3 (x - 4) 

                                = (x - 4)(x - 3).


(ii) x2 + 2x - 15

Solution:

The given expression is x2 + 2x - 15

To factorize the given quadratic trinomial, we have to find two numbers a and b, such that a + b = 2 and ab = -15

Clearly, 5 + (-3) = 2 and 5 × (-3) = -15

Therefore such numbers are 5 and -3

Now, splitting the middle term 2x of the given quadratic trinomial x2 + 2x -15, we get,

x2 + 5x - 3x -15

= x(x +5) - 3(x + 5)

= (x + 5) (x - 3)

 

(ii) Factorization of trinomial of the form ax^2 + bx + c:

In order to factorize the expression ax2 + bx + c we have to find the two numbers p and q, such that

p + q = b and p × q = ac


Solved examples on factorization of quadratic trinomials of the form ax^2 + bx + c:

2. Factorize the algebraic expression of the form ax2 + bx + c:

(i) 15x2 - 26x + 8

Solution:

The given expression is 15x2 - 26x + 8.

Find two numbers whose sum = -26 and product = (15 × 8) = 120.

Clearly, such numbers are -20 and -6.

Therefore, 15x2 - 26x + 8 = 15x2 - 20x - 6x + 8

                                   = 5x(3x - 4) - 2(3x - 4) 

                                   = (3x - 4)(5x - 2).


(ii) 3q2 – q – 4

Solution:

Here, two numbers m and n are such that their sum m + n = -1 and their product m × n = 3 × (-4) i.e. m × n = - 12

Clearly, such numbers are -4 and 3

Now, splitting the middle term –q of the given quadratic trinomial 3q2 – q – 4 we get,

3q2 - 4q + 3q – 4

= q(3q – 4) + 1(3q – 4)

= (3q – 4)(q + 1)





8th Grade Math Practice

From Factorization of Quadratic Trinomials to HOME PAGE


Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.